ปัจจัยคัดสรรที่มีความสัมพันธ์กับคุณภาพชีวิตของผู้ดูแลผู้ป่วยจิตเภทที่ให้การดูแลผู้ป่วยที่บ้าน - เอมิกา กลยนี (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purposes of this descriptive research were to study quality of life of schizophrenic patients’ caregivers and to examine relationships among age, income, duration of care, sense of coherence, health status, caregiver burden, social support and quality of life of schizophrenic patients’ caregivers. The subjects were 143 schizophrenic patients’ caregivers who took the patient visitime in Out Patients Department at a Psychiatric Clinic Regional hospitals and Medical centers selected by random sampling technique. The research instruments were the personal data record, sense of coherence questionnaires, Short Form 36 Health survey (SF-36), caregiver burden scale, social support questionnaires and World Health Organization Quality Of Life-BREF (WHOQOL-BREF-THAI). The instruments were tested for content validity by 5 professional exerts and analyzed by using Cronbach’s alpha coefficient. the scale reliability were .85, .92, .90, .92 and .93 respectively. Data were analyzed by using frequency, percent, mean, standard deviation, Pearson’s Product Moment Correlation and Chi-Square.Major findings were as follows:1. A quality of life among caregivers caring for patients with schizophrenia at home was at moderate level (Mean= 82.86, SD = 8.02).2. Sense of coherence, health status and social support of schizophrenic patients’ caregivers were positively correlated at moderate level with quality of life of schizophrenic patients’ caregivers at level of .05 (r= .583, .564 and .605 respectively).3. Age was negatively correlated at low level with quality of life of schizophrenic patients’ caregivers at level of .05 (r= -.216).4. Caregiver burden was negatively correlated at moderate level with quality of life of schizophrenic patients’ caregivers at level of .05 (r= -.629).5. Income of schizophrenic patients’ caregivers was significantly correlated with quality of life of schizophrenic patients’ caregivers at level of .05.6. Duration of care was not correlated with quality of life of schizophrenic patients’ caregivers.